Highly stable tribological performance and hydrophobicity of porous polyimide material filled with lubricants in a simulated space environment. Issue 66 (19th July 2015) - Lv, Mei; Wang, Chao; Wang, Qihua; Wang, Tingmei; Liang, Yongmin
<x xml:space="preserve">Abstract</x> Highly stable tribological and hydrophobic performance of porous polyimide material filled with lubricants in a rigorous space environment.